El beneficiario controlador y sus implicaciones en el sector primario - Rodríguez Villanueva, Luis David (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
As of January 2022, a new tax obligation was incorporated, which consists of obtaining and keeping reliable, complete and updated information from its Controlling Beneficiaries. In order to maintain timely access to such information at the time the tax authority requires it. This obligation arises in articles 32-B Ter to 32-B Quinquies of the Federal Tax Code, which is applicable to the entire national territory. In this sense, it is essential to establish and define this new concept of Controlling Beneficiary that came to impose a new obligation and therefore it is essential that companies begin to know it and become familiar with it because it is not an isolated term. For decades, international organizations have suggested to the various countries to integrate it into their regulations in order to establish standards and promote the effective application of legal, regulatory and operational measures to combat money laundering, the financing of terrorism, the proliferation of weapons of mass destruction and other threats related to the integrity of the international financial system. Therefore, in this research work it is suggested to implement internal control procedures duly supported and documented that allow the full identification of the controlling beneficiary of a company in order to comply with legal regulations.

A partir de enero de 2022 se incorporó una nueva obligación fiscal, que consiste en obtener y conservar información fidedigna, completa y actualizada de sus Beneficiarios Controladores. Con la finalidad de mantener el acceso oportuno a dicha información en el momento que la autoridad fiscal lo requiera. Dicha obligación nace en el artículo 32-B Ter a 32-B Quinquies del Código Fiscal de la Federación la cual es aplicable a todo el territorio nacional. En este sentido, es indispensable establecer y definir este nuevo concepto de Beneficiario Controlador que llegó a imponer una nueva obligación y por lo tanto es imprescindible que las empresas comiencen a conocerlo y a familiarizarse con el pues no resulta ser un término aislado. Desde hace décadas los organismos internacionales han sugerido a los diversos países integrarlo en su normativa a fin de establecer normas y promover la aplicación efectiva de las medidas legales, reglamentarias y operativas para combatir el lavado de dinero, el financiamiento al terrorismo, la proliferación de armas de destrucción masiva y otras amenazas relacionadas con la integridad del sistema financiero internacional. Por ello, en el presente trabajo de investigación se sugiere implementar procedimientos de control interno debidamente soportados y documentados que permitan la plena identificación del beneficiario controlador de una empresa a fin de cumplir con la normativa legal.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Fiscal
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2025-1079; Control; Titularidad; Identificar; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19402